HUBUNGAN MUTU PELAYANAN KEPERAWATAN DENGAN KEPUASAAN PASIEN DI RUANG RAWAT INAP RSUD SITI FATIMAH - Yuliar, Yuliar; Sumarni, Titin; Latip, Abdul (Journal Safety and Healthty, 2024)
Patient satisfaction is still a problem in several hospitals in Indonesia and even the world. This study aims to determine the relationship between service quality and patient satisfaction in the Inpatient Room of Siti Fatimah Hospital, South Sumatra Province in 2019. This type of research used cross sectional. Statistical test using chi-square test using accidental sampling with a total of 50 respondents. The analysis was carried out in two stages, namely Univariate and Bivariate analysis, the results showed that the quality of nursing services at Siti Fatimah Hospital was good. Patient satisfaction in Siti Fatimah Hospital is high. There is a relationship between the quality of nursing services with patient satisfaction in Siti Fatimah Hospital. The better the quality of nursing services provided, the higher the level of patient satisfaction with the services provided. This research is expected to be a consideration for the leadership of Siti Fatimah Hospital in improving the quality of good service to patients so that the level of patient satisfaction is high.